PENGARUH KARAKTERISTIK WIRAUSAHAWAN TERHADAP TINGKAT KEBERHASILAN USAHA - Wijayanto, Andi (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2013)
This research had been done at fish processing small industry in Krobokan Semarang. It aims to : (a) identify the profile of small industries, (b) identify the characteristics of enterpreneurs, (c) measuring the level of bussiness success, (d) examine and analyze the influence of enterpreneur Â characteristics on the level of bussiness success, and (e) find variable which has dominant effect on bussiness success. Research conducted using the survey design. The primary data obtained through questionnaires, observations, and interviews. While secondary data was obtained by using documentationÂ method. Census method was applied with consideration of the number of small populations. The study concluded that : (a) the level of bussiness success is considerably good as shown on stable sales trend and slightly increased; (b) Personal Ability and Social Ability simultaneously have significant effect on bussiness success; (c) Social Ability and Personal Ability variable partially have significant effect on the level of bussiness success; (d) Social Ability has dominant influence to the level of bussiness success.